Construction of automated optimal control systems with elements of artificial intelligence - Tsen, Khu Ven; Umarova, Zhanat; Kozhabekova, Pernekul; Suieuova, Nabat (IAES International Journal of Robotics and Automation (IJRA), 2023)
This article examines the widespread introduction of artificial intelligence technologies, means of their implementation and support as a determining factor in the development of scientific and technological progress. On this basis, various advanced objects of various functional purposes are created, which are characterized as “smart”. Their distinguishing feature is the ability to implement a “reasonable” way of functioning, taking into account the prevailing circumstances. This ability is expressed in the fact that in the object automatically, i.e., without human participation, or with minimal human participation, the most rational or optimal modes of functioning are supported, the definition of which involves the performance of operations containing signs of rational activity. This “smart” behavior of technical objects is mainly determined by the “intelligent” functioning of the control systems built into them. In particular, intelligent automated systems for optimal control. In accordance with this, the development of new approaches and methods that expand the possibilities of building such control systems should be considered as an urgent and priority task.